Assessment of oral health literacy among patients attending Malabar dental college and research centre in Kerala: A cross sectional survey - Mary Shimi S Gomez; B K Sujatha (Wolters Kluwer Medknow Publications, 2015)
Introduction: Oral health literacy is relatively a new, but critical concept to decrease disparities and increase oral health for all. Low oral health literacy contributes to oral disease which results in increased cost for vulnerable population such as poor, those with low levels of education, minorities, and the elderly. Aim: To assess oral health literacy among patients attending Malabar dental college and research centre in Kerala. Materials and Methods: Health literacy in dentistry scale questionnaire with 29 items was administered by the investigator to collect data related to oral health literacy among 272 patients attending Malabar Dental College and Research Centre. The collected data were compiled and statistically analyzed using Chi-square test. Results: The oral health literacy was assessed based on the interquartile range, of 272 patients, 23.9% of patients had poor oral health literacy, 57% were found to have moderate oral health literacy, and 19.1% patients were found to have good oral health literacy. The results were significant at P < 0.001. Conclusion: Oral health literacy was found to be moderate among patients attending Malabar Dental College and Research Centre.